Οι βουλευτικές εκλογές στην Οθωμανική αυτοκρατορία: Οι Έλληνες βουλευτές 1908-1918 - Μπούρα Κατερίνα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1983)
Although by the end of World War I the Young Turks seemed to have failed in their original objectives, the decade 1908-1918 was very significant for Turkey as well as for Hellenism in the Ottoman Empire. During this period which marked the transition of the Ottoman Empire from a “multinational” to the “national” Turkish State, the dominant political group was the Committee of Union and Progress. The Greeks under Ottoman rule took an active part in the political developments of 1908-1912. The Balkan Wars and subsequently the failure of Ottomanism, together with the collapse of ideals and hope for a peaceful coexistence of the different nationalities in the Ottoman Empire, led to an accelerated growth of Turkish national feeling — a development with disastrous effects on the fortunes of the unredeemed Greeks.